Digital dynamics in Nordic contemporary art - Toft, Tanya, 1984- (Intellect ; Intellect, The University of Chicago Press, 2019)
Affected by technology and globalization, the Nordic region is experiencing large shifts in its socio-political conditions and international outlook today. As digital dynamics affect life worlds, contemporary artists are making new inquiries in response to the changing Nordic context. As a result of these ever-evolving circumstances, conditions and motivations for making art change as well. As technology and digital culture become more deeply embedded in the contemporary art scene, there is a renewed need to examine the role of art in society and everyday life, and to consider how the digital inspires artists to evolve and tackle socio-political realities, locally and in the wider world. The first section of Digital Dynamics in Nordic Contemporary Art features a collection of testimonials from 78 artists connected to Nordic art who employ concepts and tools relating to the digital in their practice. These testimonials form the basis of essays in the book's second section, penned by leading scholars and curators of Nordic art. They investigate the digital influences on contemporary art, with particular attention paid to the national and international Nordic socio-political context.